2017
DOI: 10.1093/femsle/fnx017
|View full text |Cite
|
Sign up to set email alerts
|

Microbial succession in biofilms growing on artificial substratum in subtropical freshwater aquaculture ponds

Abstract: Biofilms can be used to improve the water quality in aquaculture ponds, and elucidating the process of microbial succession in biofilms would allow the characterization of metabolic processes and permit optimization. In the present study, microbial succession of a biofilm growing on artificial substrata in a subtropical freshwater pond was investigated by high-throughput sequencing. Providing artificial substrata effectively reduced the concentrations of total nitrogen and total phosphorus in the pond. Relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…The lower levels of ammonia nitrogen in the treatment tanks may be due to the nitrification processes facilitated by the microbial biomass attached to the plant substratum in the tanks. Li et al (2017) also reported that the provision of artificial substrata effectively reduced the concentrations of total nitrogen in freshwater aquaculture pond.…”
Section: Resultsmentioning
confidence: 94%
“…The lower levels of ammonia nitrogen in the treatment tanks may be due to the nitrification processes facilitated by the microbial biomass attached to the plant substratum in the tanks. Li et al (2017) also reported that the provision of artificial substrata effectively reduced the concentrations of total nitrogen in freshwater aquaculture pond.…”
Section: Resultsmentioning
confidence: 94%
“…Further, artificial substrata have been used in ponds to enhance the formation of biofilms that aid in controlling N and P (Li et al, 2014;Yu et al, 2016). Our previous study also showed that adding artificial substrata to an aquaculture pond could create a habitat for denitrifiers and phosphorus-removing bacteria (Li et al, 2017). In the present study, bacteria involved in N and P cycles such as Hyphomicrobium (Sperl & Hoare, 1971;van der Drift & de Windt, 1983;Brooke, Duchars & Attwood, 1987;Kloos et al, 1995), Chitinimonas (Chang et al, 2004), Legionella (Keen & Hoffman, 1984), Shewanella (Al-Harbi & Uddin, 2006;Hau & Gralnick, 2007;Fredrickson et al, 2008), Roseiflexus (Wawrik et al, 2011;Penton et al, 2013;Gerbl et al, 2014;Hug et al, 2015;Wang et al, 2018), and Planktothrix (Zotina, Köster & Jüttner, 2003;Davis et al, 2015) were enhanced on the artificial substrata and in associated pond water (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…PCR was performed in 30-l reaction volumes with 15 l of Phusion High-Fidelity PCR Master Mix (New England Biolabs, Ipswich, MA, USA), each primer at 0.2 M, and approximately ng of template DNA. Thermal cycling conditions were as reported previously (Li et al, 2017). The PCR products were mixed at ratios of equal density and the mixed PCR products were purified using the Gene JET Gel Extraction Kit (Thermo Scientific, USA).…”
Section: Microbiota Collection Dna Extraction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplification was carried out using the prokaryotic primer set 515F (5-GTG CCA 148 GCM GCC GCG GTA A-3) and 806R (5-GGA CTA CHV GGG TWT CTA AT-3) for the V4 149 region of the 16S rRNA gene, as we have described previously (Tamaki et al, 2011;Li et al, 150 2016; Li et al, 2017;Ni et al, 2018). The resulting PCR products were pooled and purified using 151 an Axygen gel extraction kit (Axygen, USA).…”
mentioning
confidence: 99%